2017
DOI: 10.1109/tfuzz.2016.2637934
|View full text |Cite
|
Sign up to set email alerts
|

Designing an Interval Type-2 Fuzzy Logic System for Handling Uncertainty Effects in Brain–Computer Interface Classification of Motor Imagery Induced EEG Patterns

Abstract: Abstract-One of the urgent challenges in the automated analysis and interpretation of electrical brain activity is the effective handling of uncertainties associated with the complexity and variability of brain dynamics, reflected in the nonstationary nature of brain signals such as electroencephalogram (EEG). This poses a severe problem for existing approaches to the classification task within brain-computer interface (BCI) systems. Recently emerged type-2 fuzzy logic (T2FL) methodology has shown a remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 53 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…10 and 11. It is confirmed from both the figures that alpha band (8-13 Hz) is associated during visual alertness and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) band is active during motor execution tasks.…”
Section: C3 Pre-processing and Filteringsupporting
confidence: 58%
See 2 more Smart Citations
“…10 and 11. It is confirmed from both the figures that alpha band (8-13 Hz) is associated during visual alertness and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) band is active during motor execution tasks.…”
Section: C3 Pre-processing and Filteringsupporting
confidence: 58%
“…The acquired EEGs from pre-frontal/frontal, parietal and motor cortex regions are pre-processed using band pass filters (BPFs) of suitable frequency bands. VA being more prominent in alpha band (~8-13 Hz) [41] and MP/ME being relatively more active in mu-(8-13 Hz) [42] and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) [43] bands, we used BPFs of required pass bands. More review on EEG channel selection and frequency band selection are provided in [44], [45].…”
Section: System Design and Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of this activity is a multiple of or the same as the frequency of the visual stimulus. Previous studies have demonstrated that EEG signals over the visual cortex are natural responses to flickering stimuli between 5 and 27 Hz, with the strongest response at frequencies approximately 15 or 20 Hz [5,6], which can be used to develop brain-computer interface applications [7,8]. Based on the behavioral characteristics of brain electrical activity, a response decrement resulting from repeated visual stimulation is defined as habituation, suggesting robustness of the brain system [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it speeds up the conventional training protocols for improved performance [13], and could be more natural and relevant for people with disability [4]. Adaptive Brain Interface (ABI) was one of the earliest examples of such BCI systems [17], later many other systems using error potential based adaptation [22], adaptive autoregressive models [23], transductive learning [24], covariate shift adaptation [18], [25], Kullback-Leiber-Common-SpatialPatterns (KLCSP) [26], interval-type-2-fuzzy classifiers [27] have been implemented.…”
mentioning
confidence: 99%